2022
DOI: 10.3389/fpls.2022.922694
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Active Human TGFβ1 in Nicotiana benthamiana

Abstract: The production of recombinant proteins in plant systems is receiving wider attention. Indeed, various plant-produced pharmaceuticals have been shown to be biologically active. However, the production of human growth factors and cytokines in heterologous systems is still challenging because they often act as complex forms, such as homo- or hetero-dimers, and their production is tightly regulated in vivo. In this study, we demonstrated that the mature form of human TGFβ1 produced and purified from Nicotiana bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The complex disulfide structure and the involvement of the propeptide in native activin formation pose a significant challenge for refolding, making this protein an intriguing candidate for testing the reverse screening approach [23]. Previous studies have demonstrated the production of human TGFβ1 in Nicotiana benthamiana, the mature form with biological activity obtained after enterokinase treatment [38]. Based on the specific cleavage property of enterokinase, the fusion protein is released after treatment with this enzyme [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The complex disulfide structure and the involvement of the propeptide in native activin formation pose a significant challenge for refolding, making this protein an intriguing candidate for testing the reverse screening approach [23]. Previous studies have demonstrated the production of human TGFβ1 in Nicotiana benthamiana, the mature form with biological activity obtained after enterokinase treatment [38]. Based on the specific cleavage property of enterokinase, the fusion protein is released after treatment with this enzyme [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Plant expression systems offer a promising solution for anti-DENV mAb production. Among these, N. benthamiana stands out as one of the most well-characterized plants for recombinant proteins synthesis, like growth factors, enzymes, antibodies, and vaccines [ 28 , 29 ]. It provides unique benefits such as low operating costs, a rapid and simple production process, high reproducibility, ease of scalability, and the ability to express complex protein [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…for easy purification and analysis. Immobilized metal-ion affinity chromatography is widely used for purification of hexahistidine tagged proteins ( Vafaee and Alizadeh, 2018 ; Islam et al., 2019 ; Hanittinan et al., 2020 ; Islam et al., 2020 ; Marques et al., 2020 ; Soni et al., 2022 ). Other techniques such as one-step cation-exchange chromatography, Protein G-/A-based affinity chromatography, diafiltration (antibody purification) and polyelectrolyte precipitation (removal of plant proteins), hydrophobic interaction chromatography (HIC) followed by hydrophobic charge induction chromatography (HCIC) are employed in recombinant plant protein purification ( Fulton et al., 2015 ; Park et al., 2015 ; Shi et al., 2019 ; Miura et al., 2020 ; Lim et al., 2022 ; Grandits et al., 2023 ).…”
Section: Systems Engineering Approaches To Produce Recombinant Biopha...mentioning
confidence: 99%